2018
DOI: 10.1111/jdi.12978
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐dependent insulinotropic polypeptide deficiency reduced fat accumulation and insulin resistance, but deteriorated bone loss in ovariectomized mice

Abstract: Given the established roles of glucose‐dependent insulinotropic polypeptide (GIP) in promoting fat storage and bone formation, we assessed the contribution of GIP to obesity and osteopenia in ovariectomized mice with a gene encoding green fluorescent protein (GFP) inserted into the GIP locus, in which GIP was either reduced (GIP gfp/+ ) or absent (GIP gfp/gfp ). In GIP gfp/gfp mice, weight gain, subcutaneous and visceral fat mass were reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, overall effects of GIP at pharmacological concentrations are likely to be protective against atherosclerosis both in non-diabetic and diabetic conditions in vivo. Furthermore, recent in vivo studies have demonstrated multiple beneficial effects of GIP on diabetes-related diseases, such as Alzheimer's disease [129][130][131][132][133][134] and osteoporosis [135][136][137][138][139][140][141][142][143][144][145][146]. These findings suggest that dual or triple agonists including GIPR, which will be available in the near future [54][55][56], could be comprehensive treatment for diabetes and its related disorders.…”
Section: Discussionmentioning
confidence: 95%
“…However, overall effects of GIP at pharmacological concentrations are likely to be protective against atherosclerosis both in non-diabetic and diabetic conditions in vivo. Furthermore, recent in vivo studies have demonstrated multiple beneficial effects of GIP on diabetes-related diseases, such as Alzheimer's disease [129][130][131][132][133][134] and osteoporosis [135][136][137][138][139][140][141][142][143][144][145][146]. These findings suggest that dual or triple agonists including GIPR, which will be available in the near future [54][55][56], could be comprehensive treatment for diabetes and its related disorders.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, postmenopausal women have increased plasma GIP levels (Ranganath et al, 1998), which are reduced by oestrogen replacement therapy (Sztefko et al, 2005). GIP receptor KO in ovariectomised mice causes, as for male mice, resistance to diet‐induced weight gain (Isken et al, 2008; Shimazu‐Kuwahara et al, 2019). Obesity treatment based on GIP receptor antagonism could therefore be of relevance to this part of the population.…”
Section: Discussionmentioning
confidence: 99%